2021
DOI: 10.3390/antibiotics10111400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metronidazole as an Adjunct to Non-Surgical Periodontal Therapy on Insulin Resistance in Type 2 Diabetics

Abstract: Treating periodontitis with metronidazole (MET) as an adjunct to scaling root planing (SRP) is suggested to have inconsistent effects on insulin resistance (IR) in type 2 diabetes mellitus (T2DM). This paper will present the effects of MET, in addition to SRP, on the homeostatis model assessment of IR (HOMA-IR). A three-arm clinical trial was conducted and analyses were performed on T2DM participants with periodontitis (n = 74) who completed follow-up visits at 3 and 6 months after the intervention. The observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…7 Therefore, clinicians only have to select conventional therapeutic strategies that involve three main steps: (1) glycemic control, (2) regular periodontal non-surgical treatment, and (3) antibiotic administration. 8,9 Although it has demonstrated a certain extent of efficacy in alleviating diabetic periodontitis (DP), 10 a plethora of related clinical trials have revealed no significant differences in the serum levels of key critical pro-inflammatory cytokines such as TNF-α and IL-6 before and after therapy. 11–13 In addition, related research studies have also claimed that this strategy played a limited role in alleviating the IR level of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Therefore, clinicians only have to select conventional therapeutic strategies that involve three main steps: (1) glycemic control, (2) regular periodontal non-surgical treatment, and (3) antibiotic administration. 8,9 Although it has demonstrated a certain extent of efficacy in alleviating diabetic periodontitis (DP), 10 a plethora of related clinical trials have revealed no significant differences in the serum levels of key critical pro-inflammatory cytokines such as TNF-α and IL-6 before and after therapy. 11–13 In addition, related research studies have also claimed that this strategy played a limited role in alleviating the IR level of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In addition, related research studies have also claimed that this strategy played a limited role in alleviating the IR level of diabetes. 8,14 What's worse, antibiotic use is not routinely recommended due to the increased bacterial drug resistance which is detrimental to the human body. 9,15 Periodontitis is caused by the confrontation between pathogenic microorganisms and various immune cells in the tissue.…”
Section: Introductionmentioning
confidence: 99%